Thioredoxin Reductase Is a Valid Target for Antimicrobial Therapeutic Development Against Gram-Positive Bacteria - Felix, LewisOscar; Mylonakis, Eleftherios; Fuchs, Beth Burgwyn (Frontiers in Microbiology, 2021)
There is a drought of new antibacterial compounds that exploit novel targets. Thioredoxin reductase (TrxR) from the Gram-positive bacterial antioxidant thioredoxin system has emerged from multiple screening efforts as a potential target for auranofin, ebselen, shikonin, and allicin. Auranofin serves as the most encouraging proof of concept drug, demonstrating TrxR inhibition can result in bactericidal effects and inhibit Gram-positive bacteria in both planktonic and biofilm states. Minimal inhibitory concentrations are on par or lower than gold standard medications, even among drug resistant isolates. Importantly, existing drug resistance mechanisms that challenge treatment of infections like Staphylococcus aureus do not confer resistance to TrxR targeting compounds. The observed inhibition by multiple compounds and inability to generate a bacterial genetic mutant demonstrate TrxR appears to play an essential role in Gram-positive bacteria. These findings suggest TrxR can be exploited further for drug development. Examining the interaction between TrxR and these proof of concept compounds illustrates that compounds representing a new antimicrobial class can be developed to directly interact and inhibit the validated target.